The artist publication as a decolonial strategy (Palíndromo, 2023)
Considering the possibilities of artistic production and circulation that artist publications offer, this article addresses the decolonial potential of these productions as an alternative to institutionalized art spaces. To do so, we formulate the following research problem: How can artist publications work as a decolonial practice for artistic circulation outside official art spaces? To answer this question, we conducted a bibliographic research aiming to discuss the art system as a colonial Heritage; conceptualize artist publications and their fruition process in unconventional spaces as a dissident practice; and present artistic propositions for circulation that go beyond institutionalized art spaces. The results of this research indicate that artist publications contribute to democratizing the access to the aesthetic experience by proposing alternative ways of circulation, consumption and production outside the institutionalized art system.
Keywords: decoloniality; art spaces; artist publication